THE ROLE OF DIGITAL TECHNOLOGIES IN TEACHING ONCOLOGY - Kobilov O. R.; Dekhkambaeva Z. A.; Dursunov S. A.; Abdurakhimova D. D. (Bright Mind Publishing, 2025)
The problem of modern oncology is the discrepancy between the achievements of medical science and technology and the understanding of general practitioners to conduct examinations and the ability to apply them and detect cancer at a stage when the cure rate can be 80-100%. It is necessary to train doctors who are not so much knowledgeable as able to determine the optimal diagnostic tactics. The interactive system allows solving tactical problems, conducting classes more vividly with visual perception and implementing an immediate objective and transparent knowledge control for participants, presenting them in the form of graphs and time spent on answers. Preliminary experience of combining traditional forms of training and modern digital technologies indicates the effectiveness of increasing oncological literacy and alertness of students and general practitioners.
Keywords: Oncological, discrepancy, medical science, clinical, digital technology.